Evidence that the stalk of Drosophila kinesin heavy chain is an alpha- helical coiled coil (The Rockefeller University Press, 1992)
Kinesin is a mechanochemical enzyme composed of three distinct domains: a globular head domain, a rodlike stalk domain, and a small globular tail domain. The stalk domain has sequence features characteristic of alpha-helical coiled coils. To gain insight into the structure of the kinesin stalk, we expressed it from a segment of the Drosophila melanogaster kinesin heavy chain gene and purified it from Escherichia coli. When observed by EM, this protein formed a rodlike structure 40- 55 nm long that was occasionally bent at a hingelike region near the middle of the molecule. An additional EM study and a chemical cross- linking study showed that this protein forms a parallel dimer and that the two chains are in register. Finally, using circular dichroism spectroscopy, we showed that this protein is approximately 55-60% alpha- helical in physiological aqueous solution at 25 degrees C, and approximately 85-90% alpha-helical at 4 degrees C. From these results, we conclude that the stalk of kinesin heavy chain forms an alpha- helical coiled coil structure. The temperature dependence of the circular dichroism signal has two major transitions, at 25-30 degrees C and at 45-50 degrees C, which suggests that a portion of the alpha- helical structure in the stalk is less stable than the rest. By producing the amino-terminal (coil 1) and carboxy-terminal (coil 2) halves of the stalk separately in E. coli, we showed that the region that melts below 30 degrees C lies within coil 1, while the majority of coil 2 melts above 45 degrees C. We suggest that this difference in stability may play a role in the force-generating mechanism or regulation of kinesin.